2019
DOI: 10.3390/rs11242989
|View full text |Cite
|
Sign up to set email alerts
|

Thermohaline Structures and Heat/Freshwater Transports of Mesoscale Eddies in the Bay of Bengal Observed by Argo and Satellite Data

Abstract: Knowledge of mesoscale eddies in the Bay of Bengal (BOB) is key for further understanding the climate variability in this region and beyond, but little is known about the vertical structure of these eddies. In this study, the three−dimensional structure and transport characteristics of mesoscale eddies in the BOB were comprehensively investigated by the combined use of Argo profiles and satellite data. The composite analysis showed that eddy−induced ocean anomalies are mainly confined to the upper 300 m of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
0
19
2
Order By: Relevance
“…Swirl transport occurs when the tracer anomalies and rotational velocities are asymmetric and, therefore, leads to net transport over the eddy wavelength (Chelton et al, 2011; Hausmann & Czaja, 2012); this process is sometimes enhanced by a series of flanking eddies (Zhan et al, 2016). Drift transport is caused by the movement of eddies when tracer anomalies inside an eddy are trapped by interior water parcels and move with the eddy (Dong et al, 2014; Lin et al, 2019). These eddy‐induced transports may exhibit comparable magnitudes (Dong et al, 2014; Sun et al, 2019), and their contribution should be jointly considered.…”
Section: Introductionmentioning
confidence: 99%
“…Swirl transport occurs when the tracer anomalies and rotational velocities are asymmetric and, therefore, leads to net transport over the eddy wavelength (Chelton et al, 2011; Hausmann & Czaja, 2012); this process is sometimes enhanced by a series of flanking eddies (Zhan et al, 2016). Drift transport is caused by the movement of eddies when tracer anomalies inside an eddy are trapped by interior water parcels and move with the eddy (Dong et al, 2014; Lin et al, 2019). These eddy‐induced transports may exhibit comparable magnitudes (Dong et al, 2014; Sun et al, 2019), and their contribution should be jointly considered.…”
Section: Introductionmentioning
confidence: 99%
“…For each Argo profile collocated within an eddy, the steric dynamic height anomaly ( h ′) is computed using the reference level at 1,000 dbar, following the definition by Gill and Niiler (1973): h=10000δρ0.25emdz ${h}^{\prime }={\int }_{-1000}^{0}\delta \rho \,dz$ where δρ is the density anomaly of an Argo profile relative to its climatological values obtained from Roemmich–Gilson Argo climatology (Roemmich & Gilson, 2009) using the method proposed by Lin et al. (2019), and dz is the vertical grid resolution. Larger values of h ′ in the subsurface compared to the surface can be representative of the subsurface maximum in velocities associated with the eddy.…”
Section: Methodsmentioning
confidence: 99%
“…𝜃 𝑒 ′ and 𝑠 𝑒 ′ are the eddy-induced potential temperature anomaly and salinity anomaly, respectively. R is the eddy region, D0 is the intergration depth (500 dbar for He and 300 dbar for Se; Lin et al (2019); Gulakaram et al (2020); also, Section 3.2). The unit of eddy heat anomaly He is J, and that of salt anomaly Se is psu•kg.…”
Section: Eddy-induced Heat and Salt Transport Estimationmentioning
confidence: 99%
“…Knowledge of the vertical structure of the ocean is vital both for comprehensive understanding of ocean dynamic processes and for analysis of the ocean circulation and energy transport. Based on satellite altimetry and Argo floats, Lin et al (2019) and Gulakaram et al (2020) showed that eddy-induced ocean anomalies in the Bay of Bengal are mainly confined to the upper 300 m and eddy thermohaline structure has a seasonal character. Cui et al (2021) Many studies examined the surface characteristics of eddies in the Bay of Bengal ans some have investigated the vertical eddy properties (Nuncio and Kumar, 2012;Dandapat and Chakraborty, 2016;Chen et al, 2012Cui et al, 2021).…”
Section: Introductionmentioning
confidence: 99%